2006
DOI: 10.1016/j.jtcvs.2005.10.003
|View full text |Cite|
|
Sign up to set email alerts
|

Brain magnetic resonance imaging abnormalities after the Norwood procedure using regional cerebral perfusion

Abstract: Ischemic lesions occur commonly in neonates with hypoplastic left heart syndrome before surgery. Despite the adoption of regional cerebral perfusion, postoperative cerebral ischemic lesions are frequent, occurring in the majority of infants after the Norwood operation. Long-term follow-up is necessary to assess the functional impact of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
163
3
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(188 citation statements)
references
References 29 publications
10
163
3
12
Order By: Relevance
“…The clinical application of NIRS is especially important in detecting hypoxia for preventing hypoxic damage in the neonatal brain. Earlier experimental and human studies in neonatal animals (1-to 3-day-old piglets) and term neonates, respectively, almost always performed with the older (adult) sensors showed that rScO 2 values <35-44% for at least 30-60 min lead to functional and/ or anatomical hypoxic brain damage (21)(22)(23). The new information gathered in this study strongly suggest that the lower limit of acceptable rScO 2 values obtained with the neonatal sensors, irrespective which NIRS device has been used, will be higher.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical application of NIRS is especially important in detecting hypoxia for preventing hypoxic damage in the neonatal brain. Earlier experimental and human studies in neonatal animals (1-to 3-day-old piglets) and term neonates, respectively, almost always performed with the older (adult) sensors showed that rScO 2 values <35-44% for at least 30-60 min lead to functional and/ or anatomical hypoxic brain damage (21)(22)(23). The new information gathered in this study strongly suggest that the lower limit of acceptable rScO 2 values obtained with the neonatal sensors, irrespective which NIRS device has been used, will be higher.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study of cerebral oxygenation in neonates with TGA undergoing an arterial switch operation showed a trend toward a less favorable neurodevelopmental outcome in neonates with a preoperative r c SO 2 <35%, as compared with neonates with a higher preoperative r c SO 2 (15). Another study in neonates with hypoplastic left heart syndrome undergoing Norwood 1 palliation showed that a prolonged r c SO 2 <45% in the postoperative period was associated with brain injury as detected on postoperative magnetic resonance imaging scans (16). In our study, the median r c SO 2 in the BAS group was 42% before BAS, which means that a considerable proportion of these neonates may have been at risk of developing brain injury.…”
Section: Discussionmentioning
confidence: 94%
“…Both measures give an impression of cerebral hypoxia and ischemia (12)(13)(14). Although previous studies have used NIRS monitoring to study cerebral oxygenation in neonates with congenital heart disease, most of this work has concentrated on intraoperative and postoperative factors (8,15,16). Little is known about the effects of preoperative interventions on cerebral oxygenation in neonates with congenital heart disease and their relationships to neonatal brain injury and neurodevelopmental outcome.…”
mentioning
confidence: 99%
“…Several studies suggested that longer duration of deep hypothermic circulatory arrest is associated with neurocognitive impairment (12)(13)(14), but despite the missing evidence of a clear time limit (12,15), perioperative seizures with impaired motor development (16) and brain damage evident on MRI were consistent with RCP as well (10,17,18). Nevertheless, improved outcome reports (early and late) about shorter postoperative ventilation, improved renal function and adequate time-related neurodevelopment have been subsequently published after using RCP (15,19,20).…”
Section: Review Articlementioning
confidence: 99%
“…Low intraoperative rSO 2 -level may impact psychomotor development (15,30,31) and correlate with postoperative cerebral lesions diagnosed by magnetic resonance imaging (15,17,18,23,(31)(32)(33). On the other hand, particularly in the context of aortic arch surgery using RCP, measuring TAV may avoid the potential dangers of excessive cerebral blood flow resulting in cerebral edema or intracranial hemorrhage (22,34).…”
Section: Review Articlementioning
confidence: 99%